Unpacking Jurassic Park Turbulence at Komodo Island: Indigenous mitigation furtherance - Sultan Bagus Firmansyah; Nokya Suripto Putri (Universitas Airlangga, 2022)
Government has set protection, conservation, resource use, education, demography, and improved management system of Komodo, Rinca, and Padar Islands development forescast via detailed blueprint entitled Jurassic Park. This Scenario evokes the exoticism of three islands “erstwhile” nature, especially as the endemic great lizard (Komodo) is there. From the outset of Komodo National Park (KNP) Involuntary enhancement, it confines 33,987 ha of Komodo, 19, 625 ha of Rinca, and 1,533 ha of Padar Islands abundant and nature resources; likewise, the 2000-2025- or 25-years masterplan of KNP, within “zoning” area, ties to limit local’s’ subsistence (i.e., sea wood harvest, aquaculture, etc.). Begun with Public-Private Partnership/PPPs, next is Indigenous Multi-corporate Enhancement/ImcE, and Mill-coalesced Indigenous Volume/Mcol. Methods of current research unveil inefficiency in coexistence with mega venture of Jurassic Park; this research advocates indigenous’ livelihood without “wasternizing” the heightens human resources, soothes internal adverse periphery and arrives at Jurassic Park renunciation nexus.